Naturvårdsavsättningar vid avverkning på Orsa Besparingsskog - Eriksson, Fredrik (SLU/School for Forest Management, 2014)
Orsa Besparingsskog has an aim to take nature considerations in relation to the harvested volume and area of the annual felling. Around 15 percent of the acreage and 10 percent of the volume should be set aside. It is important to keep close to those figures to avoid future negative effects on the long-term harvesting planning. The purpose of this study was to use laser scanning data to estimate those proportions. The result showed that the proportion of conservation considerations in the ten selected objects in the study was significantly higher than the target of 15 percent of the acreage and 10 percent of the volume. The result showed a setting aside of 19 percent of the acreage and 17 percent of the volume. This may affect the long term planning of the future harvesting negatively, since the amount of forest may not be sufficient in the long run. The variation between the ten selected objects was found to be substantial in a comparison regarding conservation considerations. The results showed a variation between 4 and 42 percent of the land area and between 4 and 43 percent of the harvested volume in the stands.